PREGNANCY OUTCOMES AND HEMOSTATIC CHANGES IN WOMEN WITH HYPERPROLACTINEMIA OF DIFFERENT ORIGINS: THE ROLE OF PREGRAVID PREPARATION (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
Hyperprolactinemia is a common endocrine disorder in women of reproductive age and is often associated with menstrual irregularities, anovulation, and infertility. The etiologies include hypothyroidism and pituitary microadenomas, each affecting reproductive function and pregnancy outcomes differently. Additionally, hyperprolactinemia may influence the hemostatic system during pregnancy, potentially increasing thrombotic risks.